Rediscovery, extended enumeration and conservation assessment of Henckelia lyrata (Gesneriaceae) in Western Ghats, India - Geethakumary, M.p.; Deepu, S.; Pandurangan, A.g.; Kumar, E.s. Santhosh (Phytotaxa, 2016)
The generic name Henckelia Sprengel (1817: 402) was proposed in honor of Leo F. V. Henckel von Donnersmark (1785–1861), a German administrator and passionate botanist. However, even though the genus had priority over Didymocarpus Wallich (1819: 378), in view of its wider usage the latter name was conserved (Vitek et al. 2000). Henckelia Sprengel (1817: 402) was resurrected from synonymy of Didymocarpus by Weber & Burtt (1997), separating them by an array of morphological characters, to give a more natural taxonomic unit. The genus Henckelia has about 180 species distributed from south India and Sri Lanka over Sumatra, southern Thailand, Malaya Peninsula, Borneo to the Philippines, Sulawesi and New Guinea. It accommodates most of the south Indian species formerly placed in Didymocarpus (Middleton et al. 2013). At present, 30 species are known to occur in India, of which 13 are endemic to the Western Ghats (Janeesha & Nampy 2015).